Combining Fractional 1927 nm Thulium Laser and Subdermal 1470 nm Diode Laser for Facial Aesthetic Procedures: Two Case Reports: Conservative facial aesthetic procedures with two lasers - Campos, Luana; Kim, Yeon Jung; Nagai, Rogério; Palma, Luiz Felipe; Moraes, Luís Otávio Carvalho de (Journal of Lasers in Medical Sciences, 2025)
Introduction: Skin aging involves a complex series of biological processes, resultingin alterations that can impact the aesthetics and well-being of patients. There has been a notable rise in the demand for safe, efficient, and effective treatments for skin aging in recent years; among them, laser-based treatments have gained rapid global popularity. Thus, the current study aimed to present two clinical cases in which a very conservative approach using a combination of laser devices was adopted to simultaneously correct certain facial aesthetic issues. Methods: Two patients sought aesthetic treatment for facial sagging, especially regarding the loss of mandibular contour due to fat accumulation in the submental region, in addition to dark spots and dark circles. The treatment proposed was performed using a combination of fractional 1927 nm thulium laser and subdermal 1470 nm diode laser in a single session. Results: Within 30 days, both patients noticed an improvement in the aesthetics of their faces, and after 90 days, there was a significant perception of reduced submental fat, facial lifting, and a reduction in facial pigmentation. Conclusion: Combining different laser wavelengths appears to be an effective, simple, and conservative option for simultaneously managing certain facial aesthetic concerns.